The Influence of Various Chloride Salts to Reduce Sodium Content on the Quality Parameters of Şalgam (Shalgam): A Traditional Turkish Beverage Based on Black Carrot - Bilal Agirman; Huseyin Erten (Journal of Food Quality)
Sodium chloride is essential in şalgam processing affecting the flavour and microbiological stability of the final product. However, reduction of sodium salt in şalgam beverage is essential due to consumers’ demand for low-sodium foods as well as recommendation of health authorities. NaCl was replaced both partially and totally by KCl and CaCl2 in the present study. Experimental design was established to investigate the effects of five different combinations (1.7% NaCl (control treatment); 0.85% NaCl–0.85% KCl; 0.85% NaCl–0.85% CaCl2; 0.85% KCl–0.85% CaCl2, and 0.56% NaCl–0.56% KCl–0.56% CaCl2) of chloride salts on microbiological, chemical, and sensory qualities of şalgam. Lactic acid bacteria (LAB) were present in populations ranging from 8.0 to 8.61 log cfu/mL while total yeasts were 6.89 to 7.12 log cfu/mL at the end of the process. The maximum number of LAB was detected in the fermentation employed NaCl + KCl salts combination. Regarding the microbiological profile, LAB growth was stimulated significantly in presence of KCl while yeast patterns were not linked to different salt treatments. The final values of total acidity (TA) and pH for şalgam were found between 7.40 and 8.71 g/L and 3.26–3.47, respectively. Concerning physicochemical attributes, pH decreased when CaCl2 increased while TA is higher in the presence of CaCl2. Şalgam juice fermented with 0.85% NaCl–0.85% KCl mineral salt combination received the best sensory results among the different salt substitutions. Results demonstrate that NaCl can be replaced in şalgam with KCl by 50%, without affecting the traditional taste of şalgam in order to meet consumers’ demand for low-sodium dietary intake.